Preexisting Heart Disease Underlies Newly Diagnosed Atrial Fibrillation After Acute Ischemic Stroke. Issue 2 (February 2016) - Rizos, Timolaos; Horstmann, Solveig; Dittgen, Felix; Täger, Tobias; Jenetzky, Ekkehart; Heuschmann, Peter; Veltkamp, Roland
Abstract : Background and Purpose—: Whether newly diagnosed atrial fibrillation (nAF) after stroke reflects underlying heart disease and represents an increased risk of cardioembolic stroke, or whether it is triggered by neurogenic mechanisms remains uncertain. We investigated, whether cardiovascular risk factors and echocardiographic parameters in patients with nAF are similar to patients with known AF (kAF) and differ from patients without AF. Methods—: Consecutive acute ischemic stroke patients were enrolled into a prospective stroke database. All patients with echocardiography were included and univariable and multivariable testing was applied to compare clinical characteristics and echocardiographic findings among patients with nAF, kAF, and no AF. Results—: A total of 1397 patients were included (male, 62.3%; median age, 71 years). AF was present in 320 (22.9%) patients. Of those, nAF was present in 36.2% (116/320) and kAF in 63.8% (204/320). No clinical or echocardiographic factor was independently associated with detection of nAF compared with kAF but a trend toward larger left atrial diameters in patients with kAF was observed ( P =0.070). In contrast, patients with nAF were more often female ( P <0.001), older ( P <0.001) and had a larger left atrial diameters ( P <0.001) compared with patients without AF. While stroke severity in patients with nAF and kAF was similar, patients without AF had less severe strokes. Conclusions—: Stroke patients with nAF and with kAF share common cardiovascular risk factors, have similar echocardiographic findings and suffer equally severe strokes. We conclude that preexisting heart disease is the major cause of AF that is first diagnosed after stroke. Abstract : Supplemental Digital Content is available in the text.